Time-Resolved Probing of the Iodobenzene C-Band Using XUV-Induced Electron Transfer Dynamics - Unwin, James; Razmus, Weronika O.; Allum, Felix; Harries, James R.; Kumagai, Yoshiaki; Nagaya, Kiyonobu; Britton, Mathew; Brouard, Mark; Bucksbaum, Philip; Fushitani, Mizuho; Gabalski, Ian; Gejo, Tatsuo; et al. (American Chemical Society, 2025)
Time-resolved extreme ultraviolet spectroscopy was used to investigate photodissociation within the iodobenzene C-band. The carbon–iodine bond of iodobenzene was photolyzed at 200 nm, and the ensuing dynamics were probed at 10.3 nm (120 eV) over a 4 ps range. Two product channels were observed and subsequently isolated by using a global fitting method. Their onset times and energetics were assigned to distinct electron transfer dynamics initiated following site-selective ionization of the iodine photoproducts, enabling the electronic states of the phenyl fragments to be identified using a classical over-the-barrier model for electron transfer. In combination with previous theoretical work, this allowed the corresponding neutral photochemistry to be assigned to (1) dissociation via the 7B2, 8A2, and 8B1 states to give ground-state phenyl, Ph(X), and spin–orbit excited iodine and (2) dissociation through the 7A1 and 8B2 states to give excited-state phenyl, Ph(A), and ground-state iodine. The branching ratio was determined to be 87 ± 4\% Ph(X) and 13 ± 4\% Ph(A). Similarly, the corresponding amount of energy deposited into the internal phenyl modes in these channels was determined to be 44 ± 10 and 65 ± 21\%, respectively, and upper bounds to the channel rise times were found to be 114 ± 6 and 310 ± 60 fs.